Penerapan Model Pembelajaran Problem Based Learning (PBL) dengan Pola Lesson Study untuk Meningkatkan Hasil Belajar Peserta Didik - Yuni Safrian Hadi; Dadi Setiadi; Ahmad Yani (Journal of Classroom Action Research, 2023)
Problem Based Learning (PBL) is a problem-based learning model that trains students to solve problems as one of the 21st century skills. Lesson Study is one of the ways to improve learning processes and outcomes conducted collaboratively and sustainably. This collaborative classroom action research aims to improve the learning outcomes of students in class X.9 SMA Negeri 1 Gerung in the 2022/2023 academic year through the application of PBL with Lesson Study patterns. Data collection techniques were observation, interview, and written test (cognitive). This research was conducted in two cycles, each cycle consisting of planning, action, observation, and reflection. Data analysis used qualitative descriptive analysis. The results showed that the application of the Problem Based Learning model through Lesson Study can improve the learning outcomes of students in class X.9 SMA Negeri 1 Gerung in the 2022/2023 academic year. This can be seen from the average value of learning outcomes in cycle I of 80 with classical completeness of 77.14% (high category) and in cycle II there was an increase with an average learning outcome of 83 with classical completeness of 85.71% (very high category). The application of the Problem Based Learning (PBL) learning model with the Lesson Study pattern can improve the learning outcomes of class X.9 students at SMA Negeri 1 Gerung for the 2022/2023 academic year.